2022
DOI: 10.47197/retos.v44i0.91907
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial status of Physical Education teachers according to socio-demographic characteristics (Condición psicosocial de los profesores de Educación Física según las características sociodemográficas)

Abstract: Currently, teachers are exposed to psychosocial risks specific to the educational context and it is important to overcome and anticipate the adversities involved. Therefore, this study aims to analyse the levels of stress, burnout syndrome and resilience in physical education teachers, as well as to establish the existing relationships according to gender and socio-occupational situation. The study had a non-experimental, descriptive, comparative and correlational design, with measurement in a single group. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Madigan and Curran (2020) affirmed that when facing an academic task, if it is prolonged over time, emotional exhaustion increases, increasing burnout levels. Likewise, it has been observed that the work and educational environments are two contexts where burnout levels increase the most due to the emotions experienced and the burnout process they cause (González-Valero et al, 2022). The research carried out by Saavedra et al (2021) found that repeating an exam to apply for a job generates emotional exhaustion the more times it is taken.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Madigan and Curran (2020) affirmed that when facing an academic task, if it is prolonged over time, emotional exhaustion increases, increasing burnout levels. Likewise, it has been observed that the work and educational environments are two contexts where burnout levels increase the most due to the emotions experienced and the burnout process they cause (González-Valero et al, 2022). The research carried out by Saavedra et al (2021) found that repeating an exam to apply for a job generates emotional exhaustion the more times it is taken.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a fundamental role in the achievement of different academic goals (Yun et al, 2020). Resilience has been observed that this ability acts beneficially in the face of negative stimuli in the academic environment (González-Valero et al, 2022). Chmitorz et al (2018) state that students who show higher levels of resilience obtain greater academic satisfaction when facing an evaluative test.…”
Section: Resilience Acts To Prevent the Onset Of Burnoutmentioning
confidence: 99%
See 2 more Smart Citations
“…In academia, Fullerton et al (2021) state that resilience plays a fundamental role in the achievement of academic goals. Similarly, Mcdermott et al (2020) and González-Valero et al (2022a) add that factors such as self-efficacy, planning, stress management and persistence play a key role in achieving academic success. Jordan et al (2020) assessed levels of burnout and resilience over the course of an academic year, concluding that stress levels increased significantly when an assessment test was approaching.…”
Section: Introductionmentioning
confidence: 99%